The student's guide to writing economics - Neugeboren, Robert H. (Routledge, 2005)
Understanding the way economists see the world is a necessary step on the way to good economics writing. This book guides students through the means and methods of economics writing, by taking a step by step approach investigating: the keys needed to succeed as a writer of economics and an overview of the writing process from beginning to end; the basic methods economists use to analyze data and communicate their ideas; suggestions for finding and focusing one's topic, including standard economic sources and techniques for doing economic research; how to write papers; and ways of citing sources and creating a bibliography. The book also contains useful appendices, which provide details of statistical sources and relevant electronic indices. Used as a standard guide for economics students at Harvard University, the book will be of immense practical use to economics students the world over.